2017
DOI: 10.1007/s13205-017-0756-z
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of indigenous Bacillus thuringiensis strains isolated from Kashmir valley

Abstract: Bacillus thuringiensis (Bt) being an eco-friendly bioinsecticide is effectively used in pest management strategies and, therefore, isolation and identification of new strains effective against a broad range of target pests is important. In the present study, new indigenous B. thuringiensis strains were isolated and investigated so that these could be used as an alternative and/or support the current commercial strains/cry proteins in use. For this, 159 samples including soil, leaf and spider webs were collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 68 publications
1
14
0
1
Order By: Relevance
“…This number of protein was similar to the result reported by Konecka et al [5]. They found crystals contained 1-8 proteins with molecular weight of 36-155 kDa isolated during epizootics in Cydia pomonella L. Reyaz et al [6] found by SDS-PAGE investigation of the spore-crystal mixture demonstrated Bt strains contained proteins of various molecular weights ranging from 150 to 28 kDa. Two protein bands at 130 kDa and 65 kDa were detected with SDS-PAGE analysis from B. thuringiensis isolated from environments of boron [15].…”
Section: 3estimated Weight Of Protein Moleculessupporting
confidence: 86%
See 2 more Smart Citations
“…This number of protein was similar to the result reported by Konecka et al [5]. They found crystals contained 1-8 proteins with molecular weight of 36-155 kDa isolated during epizootics in Cydia pomonella L. Reyaz et al [6] found by SDS-PAGE investigation of the spore-crystal mixture demonstrated Bt strains contained proteins of various molecular weights ranging from 150 to 28 kDa. Two protein bands at 130 kDa and 65 kDa were detected with SDS-PAGE analysis from B. thuringiensis isolated from environments of boron [15].…”
Section: 3estimated Weight Of Protein Moleculessupporting
confidence: 86%
“…Ninety percents of mortality in third instar larvae of diamond backmoth Plutella xylostella larvae treated for 72 hours was caused by a protein content of 11.1 g / l [16]. Research on insect bioassays with first larvae of S. litura showed that the purified Cry2Al1 was toxic to S. litura with LC 50 2.448 mg / ml [6]. Shah et al found that some isolates with cry protein range 30-150 kDa were toxic against Amsacta albistriga (Lepidoptera:Arctiidae) [17].Therefore, it was no doubt that B. thuringiensis isolates indigenous South Sumatera were toxic to diamond backmoth P. xylostella and armyworm S. litura.…”
Section: Toxicity To Target Insect and Spore Production In Growth Mediamentioning
confidence: 99%
See 1 more Smart Citation
“…Bacillus thuringiensis is a ubiquitous bacterium found in various habitats such as soil, phylloplane, dead insects, dust, spider web etc. (Mizuki et al, 1999;Asokan and Puttaswamy, 2007;Ramalakshmi and Udayasuriyan, 2010;Unalmis et al, 2015 andReyaz et al, 2017). In the present study, the isolates preserved in glycerol stocks were revived and cultured in T 3 medium.…”
Section: Resultsmentioning
confidence: 78%
“…Only bipyramidal crystals were observed in T491 and T495 whereas cuboidal crystals were observed in T489. Jain et al (2017) and Reyaz et al (2017) reported the presence of various kinds of crystals such as spherical, bipyramidal, cuboidal and irregular shapes. Earlier the predominance of bipyramidal crystals was also reported by Bernhard et al (1997), Martin and Travers (1989) and Ramalakshmi and Udayasuriyan (2010).…”
Section: Resultsmentioning
confidence: 99%